Synthesis of doped BiNbO4 photocatalysts for removal of gaseous volatile organic compounds with artificial sunlight - Ullah, R; Ang, Ming; Tade, Moses; Wang, Shaobin (Elsevier BV, 2012)
BiNbO4, metal-doped and N-doped BiNbO4 catalysts were synthesized at lower sintering temperature of 700 °C using a solution method. The materials were characterized by XRD, SEM, FTIR, and diffuse reflectance spectroscopy, and were tested in photocatalytic decomposition of gaseous toluene under either UV or visible light. Both undoped and metal ion (Ba, Ga, Sn, La, and Al) doped BiNbO4 have multiphase crystalline structures; while the nitrogen doped BiNbO4 has only triclinic structure. Among the materials, BiNbO4:Ga showed higher performance, much better than a commercial TiO2 (P25) and could decompose more than 50% toluene (100 ppm) in initial 2 h at UV irradiation. However, BiNbO4:Ba showed better activity than others and degraded 12% toluene within initial 2 h under visible light irradiation. All the BiNbO4 materials also exhibited quite stable performance in UV or visible light.